Clinical experience with romiplostim - G. B. Kuchma; L. K. Kozlova; Ye. Ye. Kuznetsova; S. B. Borisyuk (Онкогематология)
Twenty patients with primary immune thrombocytopenia (ITP) received romiplastim as a second line therapy, and 3 patients with secondary thrombocytopenia as off-label. Romiplostim appeared effective in 85 % of patients with both persistent and chronic primary ITP. In patients with resistant and refractory ITP romiplostim response has not been registered, or it was lost. Achieving complete response to romiplostim therapy allowed its cancelation in 30 % of patients while maintaining the therapeutic effect; 15 % of patients switched to the 1 injection/biweekly in doses 4–5 mg/kg. Adverse events were observed in 21 % of patients and were temporary. With long-term use drug efficacy is not reduced, and the frequency of adverse events do not increase. Short course of romiplostim was successfully applied before surgical intervention for correction of thrombocytopenia in 3 patients with rheumatic diseases.